In-situ analysis of sphalerite trace elements and sulfur isotope of the Zhaxikang Pb-Zn-Sb-Ag deposit in southern Tibet: Implications for source and mineralization process - Lan, Qing; Hu, Ruizhong; Bi, Xianwu; Xiao, Jiafei; Zhang, Zhi; Fu, Shanling (Ore geology reviews, 2024)
[Display omitted] •A simple (Fe, Mn) or coupled (Cu, Ag coupled with In, Sb, Ga, Ge, Sn) substitution for Zn was observed in sphalerite.•The Zhaxikang is a magmatism-related medium to low-temperature hydrothermal vein deposit.•The sulfur in the Zhaxikang deposit is predominantly sourced from Jurassic marine sulfate or evaporite rocks.•The metals for the Zhaxikang deposit primarily originated from the basement metamorphic rocks (gneiss) of the Greater Himalayan Crystalline complex. The metallogenesis of collisional orogen has been a significant research topic for comprehending the linkage between magmatism, metamorphism, hydrothermalism and ore deposition. In Southern Tibet, the Zhaxikang deposit is a super-large Pb-Zn-Sb-Ag polymetallic deposit with metal reserves of 2.367 Mt Zn + Pb (average grade of 6.43 %), 0.2552 Mt Sb (average grade of 1.14 %), and 2960.6 t Ag (average grade of 101.64 g/t), constituting the largest deposit within North Himalayan Metallogenic Belt. However, the metal sources of the ore-forming material and mineralization process in this deposit remain a subject of controversy due to previous studies primarily relying on a bulk analysis of sulfides, which record the mixed results of multistage mineralization and intergrown minerals of different stages. The objective of this study is to constrain the sources and mineralization process of the Zhaxikang deposit through in-situ analyses of trace elements and sulfur isotopes in sphalerite. Based on ore textures and mineral paragenesis, four mineralization stages and three generations of sphalerite deposited respectively in stage 1 (Sp1), stage 2 (Sp2), and stage 4 (Sp3), were identified. The Pb and Zn mineralization mainly occurred in stage 2, while Sb and Ag were dominantly in stage 4. The trace elements characteristics (Cd, Fe, In, Ga, Ag, Cu, Co, and Mn) observed in sphalerite indicate that the Zhaxikang deposit could be a hydrothermal vein-type deposit associated with magmatism. The δ34S values of sulfides (7.7–18.4 ‰) in the deposit generally exhibit a slight elevation compared to those (4.1–12.9 ‰) of the Jurassic Ridang Formation slate, indicating that the sulfur of the deposit primarily originated from seawater sulfate in the slate through thermochemical sulfate reduction, although a small amount of contribution from mafic rocks also existed in stage 4. The Pb isotopes in stage 2 range from 19.662 to 19.705, 15.852 to 15.865, and 40.214 to 40.283 for the ratios of 206Pb/204Pb, 207Pb/204Pb and 208Pb/204Pb, respectively, indicating that the metals primarily from the Greater Himalayan Crystalline complex (GHC) with a minor contribution from host rocks. While, the Pb isotopes in stage 4 range from 19.687 to 19.849 for 206Pb/204Pb, from 15.86022 to 15.885 for 207Pb/204Pb, and from 40.261 to 40.414 for 208Pb/204Pb, respectively, indicating that the metals originated from sulfides in the earlier stage as well as the more radiogenic GHC.